miRNA and mRNA Profiles in Ventral Tegmental Area From Juvenile Mice With Companion Communication of Improving CUMS-Induced Depression-Like Behaviors - Song, Zhenhua; Wang, Jin-hui (Frontiers in Psychiatry, 2021)
Under chronic stress, the appearance of depression-like behaviors may be related to the decline of the brain's reward circuit function which caused by long-term lack of reward. However, the effect of reward treatment on depressive-like behaviors induced by chronic stress and its molecular mechanism in the brain remain poorly understood. Here, companion communication was used as a reward to study the effect of reward on depression-like behaviors induced by chronic unpredicted mild stress (CUMS), miRNA and mRNA profiles in ventral tegmental area (VTA) relevant to stress-induced depression-like and resilient behaviors were established by high-throughput sequencing. We observed that accompanying with companion ameliorated CUMS-induced depression-like behaviors in mice, and 202 differentially expressed genes (DEGs) associated with depression-like behaviors, 27 DEGs associated with resilience and 159 DEGs associated with nature reward (companion) were identified, and 228 differentially expressed miRNAs were found to be associated with companion. Furthermore, the miRNA-mRNA network associated with companion was established in ventral tegmental area, based on the differentially expressed miRNAs and DEGS data. Altogether, our results uncover a new way to ameliorate depression-like behavior, as well as many potential drug targets to prevent or treat depression.